Analisis Hubungan antara Infrastruktur Jalan dan Tax Capacity: Studi Kasus Indonesia - Andriany, Dian; Qibthiyyah, Riatu M. (UI Scholars Hub, 2018)
The study explore the relationship between road and spending infrastructure with tax capacity in Indonesia. Using stochastic frontier analysis method and tax revenue data of 34 provinces in 2011–2016, this study confirms positive relationship between infrastructure spending and central and local tax capacity, while the availability of road infrastructure has positive significant impact only on local tax capacity. The level of income and education indicates a positive significantly e ect both on central and local tax capacity. However, the greater the dominance of the agricultural sector in the economy tends to reduce central tax capacity. Similarly, tax administration factors affect central tax capacity positively.